التنظيم القانوني للعلامات التجارية المشهورة: دراسة مقارنة - الكعبي، سليمان سالم صالح (جائزة راشد بن حميد للثقافة والعلوم, 2020)
يتناول البحث الأحكام القانونية المعمول بها بدولة الإمارات العربية المتحدة، بشأن العلامات التجارية المشهورة على وجه الخصوص، والتي لم يورد تعريفا خاصا بها، وعلى وجه العموم مختلف التشريعات المقارنة، حيث يسلط الضوء على طبيعة هذه الأحكام، ومدى مواءمتها للاتفاقات الدولية ذات الصلة، والاتجاهات الفقهية والقضائية الحديثة، هذا بالإضافة لبيان مدى مواءمتها للظروف الاقتصادية والتجارية التي شهدتها الدولة مؤخرا، والتي ستشهدها العام المقبل في ظل معرض الاكسبو، حيث قد مر ما يزيد على ربع قرن من صدور قانون العلامات التجارية، مع عدم وجود تعديلات جوهرية في أحكامه. وتنبع أهمية البحث، من أهمية العلامات التجارية بحد ذاتها، وخصوصا المشهورة منها، فهي عنوان وشعار المشروعات التجارية، والتي تنفق عليها ملايين الدولارات، لتغدو علامتها التجارية مشهورة في مختلف دول العالم، يقصدها المستهلك تحديدا ويختارها من بين غيرها من العلامات التجارية، بما يحقق لها إيرادات بملايين الدولارات، جراء هذه الشهرة. وقد قسم البحث إلى مبحثين، خصص الأول لمعايير شهرة العلامات التجارية، والأحكام الخاصة بهذه العلامات، والمتمثلة في استثنائها من مبدئي إقليمية العلامات التجارية، وتخصيص العلامات التجارية، أما المبحث الثاني فقد خصص لآليات حماية العلامات التجارية المشهورة، وذلك من خلال دعوى المنافسة غير المشروعة، ومن خلال دعوى المنافسة الطفيلية، تلتهما خاتمة تضمنت أهم لنتائج والتوصيات، ولعل أهم نتيجة يمكن الإشارة إليها هي خلو التشريع الإماراتي من تعريف العلامات المشهورة، في حين أن أهم توصية تتمثل في حث القضاء على إعمال أحكام المنافسة الطفيلية بالنسبة لدعاوى العلامات التجارية المشهورة.
The research deals with the legal provisions in United Arab Emirates, regarding famous trademarks in particular, and which did not provided by a special definition. It deals in general with various comparative legislation. It highlights the nature of these provisions, their compatibility with relevant international agreements and modern jurisprudence and judiciary trends. In addition to that, it shows its compatibility with the economic and commercial conditions experienced recently in the country and which will be experienced next year in the view of the Expo. More than 25 years had passed since the issuance of the Trademarks Law, with no fundamental amendments in its provisions. The importance of the research comes from the importance of the trademarks themselves, especially the famous ones. Those are the title and slogan of the commercial projects, on which millions of dollars are spent, so that their trademarks become famous in various countries of the world. So, consumer chose it specifically and from among other trademarks. So they will achieve millions of dollars in revenue, due to this popularity. The research has been divided into two topics. The first one is devoted to the criteria of the popularity of trademarks, provisions related to these marks, which are excluding them from the principles of regional trademarks, and the allocation of trademarks. While the second topic is devoted to the mechanisms of protecting famous trademarks, through the unfair competition lawsuit and through the parasitic competition lawsuit. A conclusion had followed the two topics which included the most important findings and recommendations. The most important result that can be referred to is the absence of the definition of famous trademarks in the Emirati legislation. While the most important recommendation is to urge the judiciary to implement the provisions of parasitic competition for famous trademarks claims.
Keywords: الدراسات القانونية -- التنظيم القانوني -- النشاط التجاري -- العلامات التجارية -- الحماية القانونية